2009
DOI: 10.1111/j.1600-0854.2009.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Articulation Between Clathrin and Retromer in Retrograde Sorting on Early Endosomes

Abstract: Clathrin and retromer have key functions for retrograde trafficking between early endosomes and the transGolgi network (TGN). Previous studies on Shiga toxinsuggested that these two coat complexes operate in a sequential manner. Here, we show that the curvature recognition subunit component sorting nexin 1 (SNX1) of retromer interacts with receptor-mediated endocytosis-8 (RME-8) protein, and that RME-8 and SNX1 colocalize on early endosomes together with a model cargo of the retrograde route, the receptor-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
150
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(168 citation statements)
references
References 55 publications
16
150
0
2
Order By: Relevance
“…Preliminary functional analysis indicates that the expression of DNAJC13 p.Asn855Ser in COS7 cells leads to accumulation of TF in endosomal compartments, suggesting interference with endosomal compartmentalization or trafficking as the pathological mechanism of disease. The importance of DNAJC13 function in endosomal trafficking is evident from several studies showing alterations in trafficking of well-known retromer cargos when its function is perturbed (13,20). The function of retromer itself is linked to PD through the observation that mutations in another retromer subunit, VPS35, can cause familial parkinsonism (6,7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary functional analysis indicates that the expression of DNAJC13 p.Asn855Ser in COS7 cells leads to accumulation of TF in endosomal compartments, suggesting interference with endosomal compartmentalization or trafficking as the pathological mechanism of disease. The importance of DNAJC13 function in endosomal trafficking is evident from several studies showing alterations in trafficking of well-known retromer cargos when its function is perturbed (13,20). The function of retromer itself is linked to PD through the observation that mutations in another retromer subunit, VPS35, can cause familial parkinsonism (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that mutations in DNAJC6 have been recently identified in juvenile parkinsonism (18), and genome-wide association studies have identified susceptibility alleles for PD at chromosome 4p16 spanning the GAK/ DGKQ locus (19). Interestingly, DNAJC13 has also been shown to interact with the retromer component sorting nexin 1 (20). The retromer generates clathrin-independent carriers that mediate retrograde targeting of selective cargo from endosomes to the trans-Golgi network (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the clathrin associated Hcs70 cochaperone RME-8 regulates endosomal trafficking of STx (Popoff et al 2009) whilst having no effect on the transport of cholera toxin (Girard et al 2005). …”
Section: Toxin Intracellular Trafficking To the Endoplasmic Reticulummentioning
confidence: 99%
“…In addition to binding Hsc70, RME-8 has also been shown to associate and co-localize with the endosome membrane remodeling component SNX1 (10,18). SNX1 when complexed with SNX2 recruits the Vps26-Vps29-Vps35 retromer trimer to form the heteropentameric coat, also known as retromer (19).…”
mentioning
confidence: 99%